Completing a Sustained Attention Task Is Associated With Decreased Distractibility and Increased Task Performance Among Adolescents With Low Levels of Media Multitasking - Brand, John; Lansigan, Reina Kato; Thomas, Natalie; Emond, Jennifer; Gilbert-Diamond, Diane (Frontiers in Psychology, 2022)
Objective: To assess distracted attention and performance on a computer following completion of a sustained attention and acute media multitasking task among adolescents with varying self-reported usual media multitasking. Methods: Eighty-six 13-17-year-olds played the video game Tetris following completion of a Go/No-go paradigm to measure sustained attention in the presence of distractors, an acute media multitasking, or a passive viewing condition. Adolescents completed the conditions on separate visits in randomized order. Sustained attention was measured within the Go/No-go task by measuring errors of omission. Distracted attention while playing the Tetris task was measured by computing eye tracking measures of attention (first fixation duration, cumulative fixation duration) to irrelevant distractor images that bordered the Tetris game. Participants also self-reported their daily media multitasking. Results: The Go/No-go task revealed important qualitative differences in sustained attention among low and high usual media multitaskers. There was a uniform improvement in sustained attention among low usual media multitaskers, demonstrated by a consistent linear decrease in omission errors (=-0.01; P<0.05). Among high usual media multitaskers, there was initially a decrease in sustained attention (=-0.01; P=0.05) followed by an increase (=0.16; P<0.001). Completing the Go/No-go task also statistically significantly reduced distractibility and increased performance while playing Tetris compared to the passive viewing condition, but only among those with low usual media multitasking (all Ps =<0.05). There was a non-statistically significant trend that completing the acute media multitask increased subsequent distractibility and performance while playing Tetris among high media multitaskers. Conclusions: In this sample of adolescents, practicing a sustained attention reduces distractibility and improve task performance among those who have low levels of usual media multitasking. Additional work is needed to determine the effect of acute media multitasking on distractibility and task performance. Additional work is needed to determine the effect of acute media multitasking on distractibility and task performance.